Multipoint Observations of the June 2012 Interacting Interplanetary Flux Ropes - Kilpua, Emilia K. J.; Good, Simon W.; Palmerio, Erika; Asvestari, Eleanna; Lumme, Erkka; Ala-Lahti, Matti; Kalliokoski, Milla M. H.; Morosan, Diana E.; Pomoell, Jens; Price, Daniel J.; Magdalenić, Jasmina; Poedts, Stefaan; et al. (Frontiers in Astronomy and Space Sciences, 2019)
In this paper we perform a detailed analysis of interplanetary flux ropes observed between June~15--17, 2012 at Venus and subsequently at Earth's Lagrange L1 point, while the observation points were separated by about 0.28~AU in radial distance and $5^{°}$ in heliographic longitude. The flux ropes were associated with coronal mass ejections (CMEs) that erupted from the Sun on June~12--14, 2012 (SOL2012-06-12, SOL2012-06-13, and SOL2012-06-14). We examine the CME--CME interactions by using in-situ observations from the almost radially aligned spacecraft at Venus and L1, as well as by using heliospheric modelling and imagery. The June~14 CME reached the June~13 CME near the orbit of Venus and significant interaction occurred before they both reached Earth. The shock driven by the June~14 CME propagated through the June~13 CME and the two CMEs coalesced, creating the signatures of one large, coherent flux rope at L1. We discuss the origin of the strong interplanetary magnetic fields related to this sequence of events, the complexity of interpreting solar wind observations in the case of multiple interacting CMEs, and the coherence of the identified flux ropes at different observation points.